2009
DOI: 10.1116/1.3273597
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and photoactivity of InTaO4 and In0.9Ni0.1TaO4 thin films prepared by electron evaporation

Abstract: InTaO 4 and In 0.9 Ni 0.1 TaO 4 thin films have been prepared by electron evaporation of successive layers of the single oxide components and posterior annealing at T Ͼ 800°C. The annealed thin films presented the monoclinic crystallographic structure typical of these mixed oxides. The electrical and optical behaviors of the films, assessed by C-V measurements, surface conductivity as a function of temperature, and UV-vis absorption spectroscopy, indicate that these oxides are wide band gap semiconductors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It should be noted that the experimentally determined 2.6 eV band gap of InTaO 4 was substantially smaller than the 3.5–3.7 eV gaps later obtained from DFT calculations despite the fact that DFT methods are known to substantially underestimate the magnitude of semiconductor band gaps. ,, On the basis of trial DFT calculations, this discrepancy was suggested , to arise from oxygen vacancies within the material, an as-yet experimentally unverified hypothesis. It has also been suggested previously that the true gap of this compound is reflected in the strong absorption feature at 4.3 eV rather than in the much weaker lower energy features, a result supported by recent reflection electron energy loss spectroscopy (REELS) studies on InTaO 4 films prepared by physical vapor deposition . Given the extensive ongoing interest in this system, we initiated a comprehensive structural and electronic characterization of pristine and Ni-doped InTaO 4 with the goal of understanding and reconciling the unusual properties reported for this system.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…It should be noted that the experimentally determined 2.6 eV band gap of InTaO 4 was substantially smaller than the 3.5–3.7 eV gaps later obtained from DFT calculations despite the fact that DFT methods are known to substantially underestimate the magnitude of semiconductor band gaps. ,, On the basis of trial DFT calculations, this discrepancy was suggested , to arise from oxygen vacancies within the material, an as-yet experimentally unverified hypothesis. It has also been suggested previously that the true gap of this compound is reflected in the strong absorption feature at 4.3 eV rather than in the much weaker lower energy features, a result supported by recent reflection electron energy loss spectroscopy (REELS) studies on InTaO 4 films prepared by physical vapor deposition . Given the extensive ongoing interest in this system, we initiated a comprehensive structural and electronic characterization of pristine and Ni-doped InTaO 4 with the goal of understanding and reconciling the unusual properties reported for this system.…”
Section: Introductionmentioning
confidence: 71%
“…It has also been suggested previously that the true gap of this compound is reflected in the strong absorption feature at 4.3 eV rather than in the much weaker lower energy features, 9 a result supported by recent reflection electron energy loss spectroscopy (REELS) studies on InTaO 4 films prepared by physical vapor deposition. 10 Given the extensive ongoing interest in this system, we initiated a comprehensive structural and electronic characterization of pristine and Ni-doped InTaO 4 with the goal of understanding and reconciling the unusual properties reported for this system. InTaO 4 crystallizes in the wolframite structure type (Figure 1) with the monoclinic space group P2/c (no.…”
Section: ■ Introductionmentioning
confidence: 99%